Single-Sex schooling at an Elite Independent School: A Multi-Methods Case Study - Robinson, Daniel B.; Hadley, Gregory R. L.; Mitton, Jennifer (Alberta Journal of Educational Research, 2024)
This article focuses upon the milieu of single-sex schooling within an elite independent school in a Canadian urban centre. This research served as an exploratory and critical examination of single-sex schooling in a specific context, and considered its relevance, pedagogical effectiveness, and ability to meet its purported goals. Using an interpretative methodological framework, and employing a multi-methods case study design, the purpose of this research was to investigate the strengths, limitations, and possibilities of single-sex schooling in a particular educational context as informed by its students, parents of students, graduates, and teachers. We found little evidence to support the idea that single-sex schooling overwhelmingly impacted student academic or social development. Implications for practice at schools offering single-sex schooling are addressed and focus upon the importance of gender-inclusive schooling; the school as the key, rather than the school’s single-sex classes; and addressing boys’ behaviour. Key words: single-sex, gender, schooling, independent school, private school Cet article se penche sur un milieu de scolarisation non mixte au sein d’une école privée élitiste d’un centre urbain canadien. Cette recherche a permis d’examiner de façon exploratoire et critique la scolarisation non mixte dans un contexte précis, ainsi que sa pertinence, son efficacité pédagogique et sa capacité à atteindre les objectifs escomptés. Par l’utilisation d’un cadre méthodologique interprétatif et le recours à une étude de cas multimodale, cette recherche poursuivait l’objectif d’examiner les forces, les limites et les possibilités de l’enseignement en milieu non mixte, dans un contexte éducatif particulier, comme le décrivent les élèves, leurs parents, les diplômés et les enseignants. À la suite de cet examen, peu de preuves viennent soutenir l’idée que la scolarisation en milieu non mixte a un impact considérable sur le développement scolaire et social des élèves. L’article traite des implications pour la pratique dans les écoles offrant une scolarisation non mixte et se concentre sur l’importance d’une scolarisation inclusive des genres, sur l’école comme étant la clé plutôt que les classes non mixtes, et à considérer le comportement des garçons. Mots clés : non mixte, genre, scolarisation, école indépendante, école privée